2018
DOI: 10.3389/fneur.2018.00499
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and Subcortical Alterations in Medication Overuse Headache

Abstract: Medication-overuse headache is an increasing problem in headache clinics and therapy includes drug withdrawal. Although it has been shown that the orbitofrontal cortex is hypo-metabolic and exhibits less gray matter in these patients the functional role of this finding is still unclear as virtually no functional imaging studies exploring withdrawal of medication have been published. We compared structural and functional magnetic resonance images of 18 patients before and after drug withdrawal with age and gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Consistent with functional data, results of structural imaging reveal abnormalities within major regions of the mesocortical-limbic circuit in patients with MOH, including less orbitofrontal cortex volume and thickness (23,24,26). Results of several studies suggest that patients with better treatment response to medication withdrawal had more orbitofrontal volume at baseline, i.e., before withdrawal compared to patients who did not respond successfully to medication withdrawal (23,25).…”
Section: Brain Structure and The Orbitofrontal Cortexsupporting
confidence: 53%
“…Consistent with functional data, results of structural imaging reveal abnormalities within major regions of the mesocortical-limbic circuit in patients with MOH, including less orbitofrontal cortex volume and thickness (23,24,26). Results of several studies suggest that patients with better treatment response to medication withdrawal had more orbitofrontal volume at baseline, i.e., before withdrawal compared to patients who did not respond successfully to medication withdrawal (23,25).…”
Section: Brain Structure and The Orbitofrontal Cortexsupporting
confidence: 53%
“…Nevertheless, available studies found that MOH reported functional change in the pain network comparing to HCs. Multiple functional connectivity abnormalities was found in the trigeminal spinal tract nucleus, operculum, secondary somatosensory cortex (Mehnert et al, 2018 ). Hypermetabolism in insula was reported (Di et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the altered brain regions, e.g. enlarged nucleus accumbens (May, 2009 ; Planchuelo-Gómez et al, 2020 ) and structural alteration in orbitofrontal gyrus (Mehnert et al, 2018 ; Planchuelo Gómez et al, 2021 ), are shared by both CM and MOH. To observe the sole neural impact associated with medication overuse, more studies comparing CM with MOH is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stimulus design is well-established and has been published multiple times elsewhere ( Stankewitz et al, 2010 ; Schulte et al, 2016 ; Mehnert et al, 2017 , 2018 , 2019 ; Mehnert and May, 2019 ). In short, the volunteers received four different stimuli (ammonia, rose scent, or air into the left nostril, and a repetitive visual stimulation at 8 Hz) with an interstimulus interval of 46 ± 9 s, where the ammonia elicits a short-lasting, stinging, or stabbing painful sensations ( Hummel and Kobal, 1992 ; Stankewitz et al, 2010 ).…”
Section: Methodsmentioning
confidence: 99%